A simplified, 96-well–adapted, ATP luminescence–based motility assay. (October 2009) - Restouin, Audrey; Aresta, Sandra; Prébet, Thomas; Borg, Jean-Paul; Badache, Ali; Collette, Yves
Directional motility assays make use of Boyden chambers or Transwell culture inserts with porous membranes that separate cells seeded in the upper chamber from a chemoattractant supplied in a lower chamber. These assays are often time-consuming and are associated with several limitations due to manual counting and inconsistent results; low signal-to-noise ratio and fluorescence interference; and high cost and the need for specific equipment. Here, we describe a simple, direct, and easy ATP luminescence–based motility assay (ALMA), which can be used for 96-well plate quantification.